2022
DOI: 10.1590/1678-4685-gmb-2022-0078
|View full text |Cite
|
Sign up to set email alerts
|

A genomic perspective on South American human history

Abstract: It has generally been accepted that the current indigenous peoples of the Americas are derived from ancestors from northeastern Asia. The latter were believed to have spread into the American continent by the end of the Last Glacial Maximum. In this sense, a joint and in-depth study of the earliest settlement of East Asia and the Americas is required to elucidate these events accurately. The first Americans underwent an adaptation process to the Americas’ vast environmental diversity, mediated by biological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 151 publications
0
3
0
Order By: Relevance
“…As a consequence of being the last step in the human journey, the Indigenous populations from America present the lowest genetic diversity among continental populations due to the limited time for diversification within the American continent and during the Beringia Standstill ( Reich et al 2012 ; Castro e Silva et al 2022 ). The Beringia Standstill refers to the genetic isolation period of the proto-American population, comprising around 8,000 yr and restricted to a land bridge that connected Asia to America during the last glaciation ( Hoffecker et al 2014 ).…”
Section: The Complex Dynamics Of Human Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of being the last step in the human journey, the Indigenous populations from America present the lowest genetic diversity among continental populations due to the limited time for diversification within the American continent and during the Beringia Standstill ( Reich et al 2012 ; Castro e Silva et al 2022 ). The Beringia Standstill refers to the genetic isolation period of the proto-American population, comprising around 8,000 yr and restricted to a land bridge that connected Asia to America during the last glaciation ( Hoffecker et al 2014 ).…”
Section: The Complex Dynamics Of Human Diversitymentioning
confidence: 99%
“…Different studies focused on Amazonian populations have elucidated how the settlement of this region occurred and the significant genetic diversity found in each area, establishing connections between geography, language, genetics, and culture among South American Indigenous populations ( Arias et al 2018 ; Gnecchi-Ruscone et al 2019 ; Barbieri et al 2019 ; Castro e Silva et al 2020 , 2021 , 2022 ). These studies demonstrated the great mobility of past native populations in South America, known for their present-day strong population structure and prevalence of small groups of individuals.…”
Section: Overlooked Human Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation